2008
DOI: 10.1007/s00586-008-0771-1
|View full text |Cite
|
Sign up to set email alerts
|

Probable risk factors for postoperative delirium in patients undergoing spinal surgery

Abstract: Postoperative delirium and its risk factors had been widely reported in several kinds of surgeries; however, there is only one known article relative to postoperative delirium in spinal surgery. We retrospectively examined the incidence of postoperative delirium and the probable risk factors in patients undergoing spinal surgery in our hospital, with the same aged non-delirium patients as controls, over a 6-month period. Studies about postoperative delirium were reviewed and referenced for variable factors col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 25 publications
2
54
2
2
Order By: Relevance
“…Twenty-seven articles were subsequently excluded from the meta-analysis: twenty-four studies were excluded because they did not contain a risk factor for delirium, one paper's full text was not available [6], one study had fewer than 100 patients [34], and one did not obtain raw data [20]. Ultimately, six trials met the inclusion criteria [13,14,19,23,24,39].The process of identifying the relevant studies is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven articles were subsequently excluded from the meta-analysis: twenty-four studies were excluded because they did not contain a risk factor for delirium, one paper's full text was not available [6], one study had fewer than 100 patients [34], and one did not obtain raw data [20]. Ultimately, six trials met the inclusion criteria [13,14,19,23,24,39].The process of identifying the relevant studies is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a number of studies have investigated the risk factors for the development of delirium after spinal surgery [13,14]. However, the results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…And the diagnostic criteria are in line with the recommendations from POCD group [7,9]. According to the studies, the Mini-Mental State Examination has been widely used for screening of dementia in Chinese [8,11].…”
Section: Cognition Measurementmentioning
confidence: 99%
“…Observations of subjects was conducted each shift and recorded using the delirium observation screening (DOS) that is developed on the basis of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) diagnostic criteria. 4,8 The DOS scale is with 13 items that can be rated as present or absent in less than 5 minutes. The highest total score is 13.…”
Section: Psychological Evaluationsmentioning
confidence: 99%
“…2,3 Although the incidence in hip and knee joint surgery has been widely reported, there are few studies regarding postoperative delirium in spine surgery. 4,5 Increasing age, blood urea levels, cardiothoracic index, hypertension, smoking habits, blood replacement during bypass, atrial fibrillation (AF), pneumonia, and blood fluid balance in the postoperative period were found to be significant risk factors for delirium by logistic regression analysis. 6 Previous reports also suggest that prior cognitive impairment and reduced hemoglobin and hematocrit levels are significant risk factors for postoperative delirium.…”
mentioning
confidence: 99%